A study on the factors that contribute to the effective knowledge sharing behaviours among bachelor of science library & information management (Hons) (IM220/IM224) students in UiTM Kedah / Mohamad Lokman Hakim Che Mohamad Khalib - Che Mohamad Khalib, Mohamad Lokman Hakim (Faculty of Information Management, 2012)
Purpose of this study is to investigate the factors that contribute to the effective knowledge sharing behaviours among students from Bachelor of Science Library & Information Management (Hons) (IM220/IM224) in UiTM Kedah. The result of this study will improve the knowledge sharing especially among students from Bachelor of Science Library & Information Management (Hons) (IM220/IM224) in UiTM Kedah. Besides, the result of this study also can inform the students about the behaviours such as self-efficacy, reward and reciprocity that contribute to the effective knowledge sharing.